Invisible minority: a constitutional study on the rights of orang asli in Peninsular Malaysia / Farah Maznah Mohd Yusof… [et al.] - Mohd Yusof, Farah Maznah; Sultan, Nurliestje Aida Iftysham; Mohd Zulkifli, Sharmaine Fairuz; Tarmizi, Farid Afwan (2011)
This research is a legal study on the main difference of rights between the rights of Natives in Sabah and Sarawak and also the rights of Orang Asli in Peninsular Malaysia. This study sets out to discover the provisions relating to the Orang Asli under the Federal Constitution. This study also seeks to discover whether there is other legislation department that protects the rights of Orang Asli. Under Article 153 of the Federal Constitution, the rights of Malays and Natives of Sabah and Sarawak are incorporated but the Article is silent on the rights of Orang Asli. We found out that there is a legislative department called the Jabatan Kemajuan Orang Asli established to protect the rights of Orang Asli. This governmental department do protect the rights of Orang Asli but it should be enforced strictly so that there would not be any oppression done to the Orang Asli.